Kinetic Monte Carlo simulations of epitaxial growth of wurtzite GaN(0001). Issue 4 (18th March 2015) - Chugh, Manjusha; Ranganathan, Madhav
Abstract: A lattice based kinetic Monte Carlo (kMC) simulation is developed to describe growth of GaN(0001) in conditions typical of a molecular beam epitaxy unit. Deposition and surface diffusion via attachment and detachment of atoms are the main processes considered in this model. The energy barriers for surface diffusion are estimated from ab‐initio density functional theory calculations. From the ab‐initio calculations, we identify a rapid motion of N atoms attached to Ga adatoms. Preliminary kMC simulation results indicate that this motion allows N adatoms to move towards their preferred positions and thereby facilitate smooth growth prior to the formation of the protective Ga adlayer which is believed to promote smooth growth under Ga rich conditions. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)